Co-electrodeposited Mesoporous PtM (M=Co, Ni, Cu) as an Active Catalyst for Oxygen Reduction Reaction in a Polymer Electrolyte Membrane Fuel Cell. (10th March 2017) - Sorsa, Olli; Romar, Henrik; Lassi, Ulla; Kallio, Tanja
Graphical abstract: Highlights: PtCo, PtNi and PtCu are synthesized by a single-step electrodeposition process. Synthesized materials are found to be mesoporous and active for oxygen reduction. Mesoporous PtCo was found to be active and durable catalyst as a fuel cell cathode. Results are compared to a nanoparticle Pt/C and similarly synthesized Pt catalyst. Abstract: Mesoporous thin films of PtCo, PtNi and PtCu are prepared by a single-step potentiostatic electrodeposition on a carbon substrate. Films are characterized by SEM, XRD, XRF and BET, and their activity for oxygen reduction reaction (ORR) is studied in an acidic three-electrode cell. The results are compared with both a commercial nanoparticle Pt/C catalyst and a Pt catalyst prepared using the same method. Additionally, the ORR activity of PtCo is studied in a fuel cell. The onset potential of ORR is found to be higher for all the electrodeposited catalysts compared to commercial Pt/C. The ORR activity of mesoporous Pt is found to be linearly dependent on the amount of deposited platinum within a platinum loading range of 0.1−0.5 mg cm −2 . All the mesoporous catalysts exhibited higher mass activity towards ORR than commercial Pt/C. Of the studied catalysts, PtCo is found to have the highest durability. Similar results are obtained in fuel cell experiments as PtCo exhibits enhanced durability and activity towards ORR, peak powers being 60, 70 and 90 mW gPt −1 for commercial Pt/C, mesoporous Pt and mesoporous PtCo, respectively.